Study protocol to investigate the efficacy of confocal laser endomicroscopy-based selective single-elimination diet over standard fivefold elimination diet in patients with endomicroscopically proven food intolerance: app-assisted, monocentric, double-blind, randomised and controlled trial in Germany - Inke R König; Torsten Schröder; Nicole Hessler; Christian Sina; Stephan C Bischoff; Anna Kordowski; Jill Sasse; Greta Ahlemann; Franziska Schulz; Anna Exner; Lennart Jablonski; Uta Jappe; et al. (BMJ Open, 2023)
Introduction Imprecise nutritional recommendations due to a lack of diagnostic test accuracy are a frequent problem for individuals with adverse reactions to foods but no precise diagnosis. Consequently, patients follow very broad and strict elimination diets to avoid uncontrolled symptoms such as diarrhoea and abdominal pain. Dietary limitations and the uncertainty of developing gastrointestinal symptoms after the inadvertent ingestion of food have been demonstrated to reduce the quality of life (QoL) of affected individuals and subsequently might increase the risk of malnutrition and intestinal dysbiosis. This trial aims to investigate the effects of a tailored diet based on the confocal laser endoscopy (CLE) examination result to limit the side effects of unspecific and broad elimination diets and to increase the patient’s QoL.Methods and analysis The study is designed as a prospective, double-blind, monocentric, randomised and controlled trial conducted at the University Hospital of Schleswig-Holstein, Campus Lübeck, Germany. One hundred seventy-two patients with non-IgE-related food allergies and positive CLE results will be randomised to either a tailored diet or a standard fivefold elimination diet. The primary endpoints are the difference between the end and the start of the intervention in health-related QoL and the sum score of the severity of symptoms after 12 weeks. Key secondary endpoints are changes in the severity of symptoms, further QoL measurements, self-assessed state of health and number of days with a pathologically altered stool. Microbiome diversity and metabolome of stool, urine and blood will also be investigated. Safety endpoints are body composition, body mass index and adverse events.Ethics and dissemination The study protocol was accepted by the ethical committee of the University of Lübeck (AZ: 22-111) on 4 May2022. Results of the study will be published in peer-reviewed journals and presented at scientific meetings.Trial registration number German Clinical Trials Register (DRKS00029323).